2001
DOI: 10.1103/physreve.65.011106
|View full text |Cite
|
Sign up to set email alerts
|

Mode-coupling theory for multiple-point and multiple-time correlation functions

Abstract: We present a theoretical framework for higher-order correlation functions involving multiple times and multiple points in a classical, many-body system. Such higher-order correlation functions have attracted much interest recently in the context of various forms of multi-dimensional spectroscopy, and have found an intriguing application as proposed measures of dynamical heterogeneities in structural glasses. The theoretical formalism is based upon projection operator techniques which are used to isolate the sl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 61 publications
1
54
0
Order By: Relevance
“…31 The effect of the nonlinear polarizabilities in real systems, i.e., liquid Xe, CS 2 , and water, was first analyzed by using normal mode description. [42][43][44][45][46][47][48][49] In particular, Denny and Reichman successfully reproduced the 2D-Raman signal of liquid Xe based on the mode coupling theory by using the factorizing 32 Ma and Stratt found that a clear echo signal of the 2D-Raman response exists in the instantaneous normal mode description of liquid Xe, but disappears when the full molecular dynamics ͑MD͒ calculation is employed.…”
Section: Introductionmentioning
confidence: 99%
“…31 The effect of the nonlinear polarizabilities in real systems, i.e., liquid Xe, CS 2 , and water, was first analyzed by using normal mode description. [42][43][44][45][46][47][48][49] In particular, Denny and Reichman successfully reproduced the 2D-Raman signal of liquid Xe based on the mode coupling theory by using the factorizing 32 Ma and Stratt found that a clear echo signal of the 2D-Raman response exists in the instantaneous normal mode description of liquid Xe, but disappears when the full molecular dynamics ͑MD͒ calculation is employed.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several sophisticated mode-coupling approaches have been formulated to compute corrections to a Gaussian theory. 36,37 One may view both the ''primitive'' INM method and the molecular hydrodynamic theory presented in this work as 0th-order theories from which corrections may be incorporated. The molecular hydrodynamic approach provides a vastly more successful 0th-order starting point than the primitive INM theory, and, in some respects, slightly better results than the anharmonic INM theory.…”
Section: Discussionmentioning
confidence: 99%
“…[73][74][75][76][77][78] There exist promising theoretical treatments for the multi-time correlation function based on the mode-coupling theory. 79,80 These techniques have now become powerful and standard tools to study condensed phase dynamics. For example, there are often used to study the ultrafast dynamics of liquid water.…”
Section: B Why Use a Multi-time Correlation?mentioning
confidence: 99%